2019
DOI: 10.1007/s10453-019-09567-1
|View full text |Cite|
|
Sign up to set email alerts
|

The variability of pollen concentrations at two stations in the city of Wrocław in Poland

Abstract: The aim of the study was to investigate the variability of Alnus and Corylus pollen concentrations at two stations located in the city of Wrocław, Poland-one at the city centre and the other 4 km from the city centre. Our goal was to compare measurements from these stations in relation to meteorology and land cover. We used Spearman's correlation coefficient to investigate any dependence between meteorological factors and pollen concentration. Additionally, to check the relation between the direction of inflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…This contributed to a very similar pattern of pollen seasons in almost every region of Poland (Rapiejko et al 2018). We think that such a remarkable increase in temperature, as well as the high solar radiation and extended duration of sunlight, most probably caused the intense pollen release (Bilińska et al 2019). Furthermore, the peak airborne pollen concentrations were recorded on the same days at almost all locations (Rapiejko et al 2018).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This contributed to a very similar pattern of pollen seasons in almost every region of Poland (Rapiejko et al 2018). We think that such a remarkable increase in temperature, as well as the high solar radiation and extended duration of sunlight, most probably caused the intense pollen release (Bilińska et al 2019). Furthermore, the peak airborne pollen concentrations were recorded on the same days at almost all locations (Rapiejko et al 2018).…”
Section: Discussionmentioning
confidence: 63%
“…In the areas of the city where alder trees are not grown, the number of pollen grains deposited on snow was remarkably lower than those recorded among samples collected at sites where alders are grown in large numbers. Similar to Bilińska et al (2019), we assume that in spite of the enormous dispersal capacity of pollen grains, local vegetation is the main source of airborne pollen. The differences observed in the deposition of pollen among subsamples could be attributed to local conditions, such as the height and layout of buildings, and type of land use.…”
Section: Discussionmentioning
confidence: 99%
“…Application of this method eliminates low concentrations of pollen at the beginning and end of the season, which usually originate from long-distance transport or redeposition [ 32 – 34 ]. This method is the most frequently used in aerobiological studies [ 5 , 35 – 40 ]. However, other direction of research may be based on the use of different approaches, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The allergenic symptoms depend on pollen concentration (Rapiejko et al, 2007), whereas pollen concentration can vary greatly, depending on the vegetation's composition (Bilin ´ska et al, 2019a(Bilin ´ska et al, , 2019bCharalampopoulos et al, 2018;Myszkowska et al, 2010) and meteorology, i.e. temperature, wind speed, relative humidity (Kaszewski et al, 2008;Majeed et al, 2018;Puc et al, 2015).…”
mentioning
confidence: 99%
“…temperature, wind speed, relative humidity (Kaszewski et al, 2008;Majeed et al, 2018;Puc et al, 2015). Previous studies have shown that even pollen stations located close to each other may differ significantly with regard to the amount of pollen (Bilin ´ska et al, 2019a(Bilin ´ska et al, , 2019b. In this case, the modelling of pollen distribution is very important, especially for people allergic to it.…”
mentioning
confidence: 99%